Analisa Yuridis Penegakan Hukum Tindak Pidana Perjudian Online - Amin, Lalu Muh; Harun, Rina Rohayu; Ufran, Ufran (Universitas Muhammadiyah Yogyakarta, 2025)
The phenomenon of online gambling has become increasingly widespread in recent times and has brought many negative impacts that affect all aspects of life. This cannot be separated from the development of technology and information so that it brings convenience and changes to the nature of gambling crimes that were previously carried out conventionally, traditionally, to become more modern and sophisticated. This research is a type of normative legal research using a statute approach, a conceptual approach, and a case approach. The results of this study indicate that the enforcement of online gambling crimes based on the three Decisions of the Mataram District Court, namely Decision Number: 417 / Pid.B / 2023 / PN Mataram, Decision Number: 357 / Pid.B / 2023 / PN Mataram, and Decision Number 363 / Pid.B / 2024 / PN Mataram, it is known that all three are based on the provisions of Article 303 paragraph (1) 1 of the Criminal Code and Article 303 paragraph (1) 2 of the Criminal Code. Should refer to the principle of lex specialis then the law enforcement of online fraud crimes can be applied Article 27 paragraph (2) of the ITE Law which is more fulfilling and in accordance with the trial facts contained in the three Decisions at the Mataram District Court